2015
DOI: 10.1002/dvdy.24258
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling regulates dental papilla formation and tooth size during zebrafish odontogenesis

Abstract: Background Intercellular communication by the hedgehog cell signaling pathway is necessary for tooth development throughout the vertebrates, but it remains unclear which specific developmental signals control cell behavior at different stages of odontogenesis. To address this issue, we have manipulated hedgehog activity during zebrafish tooth development and visualized the results using confocal microscopy. Results We first established that reporter lines for dlx2b, fli1, NF-κB, and prdm1a are markers for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…It has also been demonstrated that crown size depends on the contact area between the Shh-expressing inner enamel epithelium and the dental mesenchyme [54]. These findings indicate that Shh signaling may regulate cellular proliferation in the dental mesenchyme, thereby controlling tooth morphogenesis [38,41,58].…”
Section: Shh Signaling Functions In the Dental Mesenchyme And Is Invomentioning
confidence: 90%
“…It has also been demonstrated that crown size depends on the contact area between the Shh-expressing inner enamel epithelium and the dental mesenchyme [54]. These findings indicate that Shh signaling may regulate cellular proliferation in the dental mesenchyme, thereby controlling tooth morphogenesis [38,41,58].…”
Section: Shh Signaling Functions In the Dental Mesenchyme And Is Invomentioning
confidence: 90%
“… Note : (−), no expression; (+), expression; †, conflicting expression data; (1), Holland et al ., 1987; (2), Lukinmaa et al ., 1993; (3), Vainio et al ., 1993; (4), Robinson & Mahon, 1994; (5), Bitgood & McMahon, 1995; (6), Mitsiadis et al ., 1995a; (7), Mitsiadis et al ., 1995b; (8), Vaahtokari et al ., 1996; (9), Åberg et al ., 1997; (10), Neubüser et al ., 1997; (11), Hardcastle et al ., 1998; (12), Jernvall et al ., 1998; (13), Keränen et al ., 1998; (14), Kettunen et al ., 1998; (15), Kettunen & Thesleff, 1998; (16), Kettunen et al ., 2000; (17), St. Amand et al ., 2000; (18), Tucker et al ., 2000; (19), Zhao et al ., 2000; (20), Laurikkala et al ., 2001; (21), Åberg et al ., 2004; (22), Fraser et al ., 2004; (23), Jackman et al ., 2004; (24), Borday‐Birraux et al ., 2006; (25), Fraser et al ., 2006a; (26), Fraser et al ., 2006b; (27), Wise & Stock, 2006; (28), Debiais‐Thibaud et al ., 2007; (29), Debiais‐Thibaud et al ., 2008; (30), Fraser et al ., 2008; (31), Jackman et al ., 2010; (32), Fraser et al ., 2013; (33), Yu et al ., 2015.…”
Section: Methodological Limitation Linked To Developmental Staging Inmentioning
confidence: 99%
“…(c) Green fluorescent protein fluorescence and alizarin red S staining Amplification of GFP fluorescence with immunohistochemistry and alizarin red S staining of mineralized teeth was performed as in Yu et al [41]. To combine the two visualization methods in a single specimen, alizarin staining was done subsequent to the antibody label.…”
Section: (B) Zebrafish Assaysmentioning
confidence: 99%